Contribution to the Valorization of Granulated Blast Furnace Slag in Soil Stabilization - Djouimaa, Sarah; Missaouri, Sabrina; Handel, Naoual; Sid, Madani (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The treatment of expansive soil is generally the most effective process for the stabilization of swelling clay. In this work, we will investigate the influence of the treatment of an expansive soil using granulated blast furnace slag (GGBS) alone and granulated blast furnace slag activated by cement (GGBS/C) by mechanical, physical and chemical tests.
Keywords: swelling pressure; granulated blast furnace slag; cement; stabilization; SEM analysis; ciśnienie pęcznienia; żużel granulowany; stabilizacja; analiza SEM